Perkembangan Biotipe Hama Wereng Coklat pada Tanaman Padi - Baehaki S. E. (Iptek Tanaman Pangan, 2012)
The Brown planthopper (BPH) had attacked rice in Darmaga-Bogor since 1939, followed attacks in Yogyakarta and Mojokerto in 1940. In 1967, Indonesian goverment introduced high yielding rice varieties IR5 and IR8 with no resistance gene against BPH. In 1971 the explosion of BPH occured, because the BPH produced biotype 1. In 1975, to overcome the BPH biotype 1 outbreak, variety IR26 carrying resistant genes Bph1 was introduced, but in 1976 again an outbreak of BPH occured due to the BPH population had changed from biotype 1 to biotype 2. In 1980, to overcome the BPH biotype 2 rice variety IR42 (with resistant genes bph2) was introduced from IRRI, but in 1981 the outbreak occurred in Simalungun, North Sumatra and some other areas, because the BPH population had changed from biotype 2 to biotype 3. To overcome the BPH biotype 3 rice variety IR56 (Bph3 resistance gene) had been introduced in 1983 and rice variety IR64 carrying resistant genes Bph1+ in 1986. In 1991 seed of variety IR74 carrying resistant genes Bph3 was distributed. In 2006, resistance gene for BPH population in IR64 had brokendown, due to BPH population had changed to biotype 4. The stability of BPH biotype 0 had survived for 41 years before becoming BPH biotype 1. Changes of BPH biotype 1 to BPH biotype 2 took just four years, and changes of BPH biotype 2 to BPH biotype 3 required of only 5 years. Stability of BPH biotype 3 was the longest, from 1981 up to 2005, or about 24 years, of which the BPH population stable in biotype 3. The occurance of BPH biotype 3 was quite long times, due to the double genes resistant on variety IR64 (Bph1+) which resulted in a sustainable, durable resistance, acting as a buffer against the changes in BPH to more higher order of biotype. To stabilize the state of BPH biotype, various strategies are recommended, including varietal rotations and growing many varieties in one area to prevent a directional selection against new BPH biotype. Growing variety containing resistance gene to higher order of BPH is also prohibited.